2020
DOI: 10.1002/bse.2600
|View full text |Cite
|
Sign up to set email alerts
|

Critical success factors for a circular economy: Implications for business strategy and the environment

Abstract: Eco-efficiency and resource optimization for business strategy and the environment can be achieved by the circular economy (CE) practices in supply chains (SCs). The leather industry is a significant industrial contributor to the economic growth of some countries, but at the same time, it leads to tremendous environmental pollution. This research focuses on the identification and evaluation of critical success factors (CSFs) needed in the business strategy development of CE practices as well as to minimize env… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
130
0
4

Year Published

2020
2020
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 185 publications
(139 citation statements)
references
References 110 publications
5
130
0
4
Order By: Relevance
“…Fuente: elaboración propia con base en los autores consultados Estudios más recientes señalan distintos factores en los sistemas y prácticas de EC, capacidades como las prácticas de desempeño ambiental, responsabilidad social empresarial, políticas de contabilidad ambiental y demandas de los grupos de interés se relacionan con el alcance de EC de las empresas y la eco innovación (Scarpellini et al, 2020a(Scarpellini et al, , 2020b. En efecto, las motivaciones, el liderazgo y compromiso de los directivos, propietarios y accionistas de las empresas y, la influencia de los grupos de interés son los factores que inciden en la implementación de sistemas de EC (Chiappetta, et al, 2020;Moktadir et al, 2020;Singhal, 2020).…”
Section: Prácticas De Economía Circularunclassified
See 2 more Smart Citations
“…Fuente: elaboración propia con base en los autores consultados Estudios más recientes señalan distintos factores en los sistemas y prácticas de EC, capacidades como las prácticas de desempeño ambiental, responsabilidad social empresarial, políticas de contabilidad ambiental y demandas de los grupos de interés se relacionan con el alcance de EC de las empresas y la eco innovación (Scarpellini et al, 2020a(Scarpellini et al, , 2020b. En efecto, las motivaciones, el liderazgo y compromiso de los directivos, propietarios y accionistas de las empresas y, la influencia de los grupos de interés son los factores que inciden en la implementación de sistemas de EC (Chiappetta, et al, 2020;Moktadir et al, 2020;Singhal, 2020).…”
Section: Prácticas De Economía Circularunclassified
“…Diversas investigaciones buscan proporcionar modelos de gestión y control a las empresas y marcos de políticas públicas para los gobiernos para incentivar y regular los sistemas de EC (Scarpellini et al, 2020b;Singhal, 2020). Así mismo, señalan la necesidad de una capacitación en las empresas, de legislaciones claras y apoyos económicos públicos para la implementación de estos sistemas de EC (Chiappetta et al, 2020;Moktadir et al, 2020).…”
Section: Prácticas De Economía Circularunclassified
See 1 more Smart Citation
“…The study highlighted various barriers and challenges in the adoption of CE and sustainable practices while suggesting solutions to tackle those challenges. Moktadir et al (2020) presented and analysed critical success factors (CSFs) of CE practices in the leather industry. The study identified CSFs of CE practices from a literature review and in consultation with domain experts.…”
Section: Previous Literaturementioning
confidence: 99%
“…Being aware of the societal need for the fashion industry to move away from a linear to a circular economy (Moktadir et al, 2020; Stewart & Niero, 2018), the industry has recently made tremendous plans and implementation strategies so that the fashion‐related economy can become more circular. In practice, circular fashion (CF) business strategies hinge on three principles (Ki et al, 2020).…”
Section: Introductionmentioning
confidence: 99%